HIV and metabolic syndrome in an Ethiopian population - Sanne Pagh Møller; Hiwot Amare; Dirk Lund Christensen; Daniel Yilma; Alemseged Abdissa; Henrik Friis; Daniel Faurholt-Jepsen; Mette Frahm Olsen (Taylor & Francis Group, 2020)
Background The global prevalence of metabolic syndrome (MS) is increasing due to lifestyle changes. Studies have found that MS is associated with human immunodeficiency virus (HIV) and antiretroviral treatment (ART), but controversies still exist on associations between HIV and MS. Aims To assess associations between HIV and MS among ART-naïve HIV positive individuals compared to HIV negative individuals. Subjects and methods A cross-sectional study among ART-naïve HIV positive and HIV negative individuals recruited from HIV treatment and testing facilities in Ethiopia. Information was collected on components of MS: waist circumference, triglycerides, high-density lipoprotein cholesterol (HDL-C), blood pressure and fasting plasma glucose (FPG). Data were analysed using logistic and linear regression stratified by sex and adjusted for age, wealth and education. Results Data from 329 HIV positive and 100 HIV negative individuals were included. HIV positive status was associated with higher odds of MS in women (OR: 3.56, 95%CI: 1.25; 10.15) (n = 292), but not in men (OR: 0.98, 95%CI: 0.22; 4.30) (n = 137), interaction: p= .11. Associations between HIV and components of MS were strongest for HDL-C among women and for FPG among men. The most prevalent components of MS in HIV positive individuals were elevated triglycerides, reduced HDL-C and elevated FPG. Conclusions HIV was associated with MS among ART-naïve women, suggesting that MS should be evaluated before initiating ART and monitored during treatment to identify those at risk of developing diabetes and cardiovascular disease (CVD).